Studying classroom climate effects in the context of multi-level structural equation modelling: an application-focused theoretical discussion and empirical demonstration. Issue 4 (7th August 2020) - Bardach, Lisa; Yanagida, Takuya; Lüftenegger, Marko
ABSTRACT: The present article focuses on classroom climate effects in the context of multi-level structural equation modelling. We first discuss the need to appropriately model classroom climate as a classroom-level construct. We then analyse the effects of classroom climate (academic goal structures and social goal structures) on students' motivation in terms of achievement goals (mastery goals) in an empirical demonstration. This study relies on doubly latent multi-level structural equation modelling and draws on a sample of 1, 645 Austrian secondary school students (52.8% girls, mean age = 14.32 years, SD = 1.42) from 83 mathematics classes. In addition, we address the question of whether and to what extent the results and interpretation differ if single-level analyses that solely account for the nested data structure by correcting standard errors are employed. Comparing the multi-level structural equation modelling results to the single-level results underlines the necessity of adequately disentangling effects at different levels. Our work is intended to raise awareness of how methodological choices affect substantive interpretations in classroom climate research, and to inform and provide guidance to (applied) researchers interested in studying the effects of classroom climate using multi-level structural equation modelling.